Optimization of radiation settings for angiography using 3D fluoroscopy for imaging of intracranial aneurysms. Issue 1 (1st January 2021) - Linsenmann, Thomas; März, Alexander; Dufner, Vera; Stetter, Christian; Weiland, Judith; Westermaier, Thomas
Abstract: Mobile 3D fluoroscopes have become increasingly available in neurosurgical operating rooms. We recently reported its use for imaging cerebral vascular malformations and aneurysms. This study was conducted to evaluate various radiation settings for the imaging of cerebral aneurysms before and after surgical occlusion. Eighteen patients with cerebral aneurysms with the indication for surgical clipping were included in this prospective analysis. Before surgery the patients were randomized into one of three different scan protocols according (default settings of the 3D fluoroscope): Group 1: 110 kV, 80 mA (enhanced cranial mode), group 2: 120 kV, 64 mA (lumbar spine mode), group 3: 120 kV, 25 mA (head/neck settings). Prior to surgery, a rotational fluoroscopy scan (duration 24 s) was performed without contrast agent followed by another scan with 50 ml of intravenous iodine contrast agent. The image files of both scans were transferred to an Apple PowerMac ® workstation, subtracted and reconstructed using OsiriX ® MD 10.0 software. The procedure was repeated after clip placement. The image quality regarding preoperative aneurysm configuration and postoperative assessment of aneurysm occlusion and vessel patency was analyzed by 2 independent reviewers using a 6-grade scale. This technique quickly supplies images of adequate quality to depict intracranial aneurysms and distal vessel patency after aneurysm clipping. Regarding these features, a further optimization to our previous protocol seems possible lowering the voltage and increasing tube current. For quick intraoperative assessment, image subtraction seems not necessary. Thus, a native scan without a contrast agent is not necessary. Further optimization may be possible using a different contrast injection protocol.